Analisis Kebutuhan Dalam Menggunakan Jasa Bank Emok Pada Masyarakat Desa Tanjung Kecamatan Banyusari Kabupaten Karawang - Cindy Safiatun Nazihah; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The need that encourages the community to get money quickly makes the people of Tanjung Village make loans to the emok bank. The purpose of this research is to find out what needs affect the village community in using emok bank services for the people of Tanjung Village. This type of research is qualitative with a descriptive approach. Data collection techniques were obtained from interviews, field observations and documentation. The results of the study show that the most basic needs for people to borrow from Bank emok include primary and secondary needs where people need food, clothing and shelter as well as secondary needs such as needing home furnishings to support their businesses such as blenders, stoves and other necessities. Another reason that makes people borrow funds from emok banks is supporting needs such as education, health and business capital. Keywords: Needs, Society, Emok bank loans